2002
DOI: 10.1207/s15389286ajde1603_3
|View full text |Cite
|
Sign up to set email alerts
|

University Instructor Perceptions of the Use of Asynchronous Text-Based Discussion in Distance Courses

Abstract: This study was conducted to extend our understanding of the impacts on instruction when asynchronous text-based Internet communication technology is integrated into distance courses. The researchers interviewed twelve university instructors to examine Berge's (1995) four roles of the use of technologies as an interview guide. Moore's (1972) theory of transactional distance was used to interpret the data. The results revealed that as university instructors in distance education programs gain experience, they fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 4 publications
4
48
1
1
Order By: Relevance
“…Technology is becoming integral to the teaching-learning process as ongoing advancements offer new avenues for learning (Burge & Haughey, 2001;DeBard & Guidera, 2000). Online learning and the use of computer-mediated communication (CMC) tools are fast growing in popularity in higher education contexts (Burbules & Callister, 2000;Kanuka, Collett, & Caswell, 2002;Rovai, 2002). However, the adoption of this medium in the teaching-learning process has quickly outpaced our knowledge regarding how it might best be used Garrison, Cleveland-Innes, Koole, & Kappelman, 2006;Pawan, Paulus, Yalcin, & Chang, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Technology is becoming integral to the teaching-learning process as ongoing advancements offer new avenues for learning (Burge & Haughey, 2001;DeBard & Guidera, 2000). Online learning and the use of computer-mediated communication (CMC) tools are fast growing in popularity in higher education contexts (Burbules & Callister, 2000;Kanuka, Collett, & Caswell, 2002;Rovai, 2002). However, the adoption of this medium in the teaching-learning process has quickly outpaced our knowledge regarding how it might best be used Garrison, Cleveland-Innes, Koole, & Kappelman, 2006;Pawan, Paulus, Yalcin, & Chang, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Kanuka, Collet and Caswell (2002) revealed that before teaching an online course the faculties are more concerned with the structural and dialogic issues such as technological operations and creating collegial relationships; the later being more challenging. In this study the faculty confessed that they were beginning to see the students as email addresses or "little red flags" rather than people, and they missed seeing the physical features, paralinguistic cues, and other types of changes that people make over a semester.…”
Section: Questions On Learners' Autonomy and Mutual Respectmentioning
confidence: 99%
“…Instructors reported difficulty in knowing when to give feedback to the group and when to give it individually by e-mail. As observed by Kanuka, Collet and Caswell (2002) separation of learners and teachers can negatively affect the teaching and learning interaction, because it creates psychological and communication spaces that can potentially lead to misunderstanding between the inputs of instructors and those of the learners.…”
Section: Questions On Learners' Autonomy and Mutual Respectmentioning
confidence: 99%
“…However, instructors can lessen transactional distance by developing dialogue and structure that match learners" needs and abilities (Kanuka, Collett & Caswell, 2002). This is even more important because irrespective of the mode of delivery, 16 students spend more time interacting with their learning material than with the lecturers (Bates, 2005).…”
Section: The Conformance Of An Institution's Goals Process and Inputmentioning
confidence: 99%